A Theologian Today. Identity and Spirituality of a Theologian in Pope Francis' Statements - Zatwardnicki, Sławomir (Teologia w Polsce, 2020)
The author arranged Pope Francis’ statements drawing a portrait of a theologian, and then on their basis characterized the spirituality of the person involved in scientia fidei. The theologian, according to the Holy Father, encountered Christ personally and cannot live without Him. United with the Son, he participates in His knowledge of the Father. The successor of St. Peter demands from the Catholic theologian existential orthodoxy, which is the sine qua non condition of practising orthodox theology. The spirituality of the theologian is inscribed in the “missionary spirituality” proposed to the whole Church; the theologian should be personally involved in the work of evangelization. The Pope also emphasizes the connection between the doctrine of faith and the spiritual life or even with holiness. The theologian, open to Deus semper maior, prays on his knees, but includes in his or her prayer the affairs of the people; his or her reflection is on the border between the Revelation and reality. The soul of theology is not only to listen to the Word of God, but also to take into account the “hermeneutical value” of the People of God. Francis urges us to abandon the theology done only “from behind the desk.” The theologian’s spirituality must include the willingness to be permeated with the smell of the people and the street.